A atuação multifacetada do percussionista: desafios de performance em três obras para percussão solo - Monica Rocio Navas Loma (2016)
This paper discusses the interaction between the contemporary percussionist and other areas of knowledge, in function of the repertory requirements around the second half of the twentieth century onwards. To describe this interaction we will adopt the concept of percussionist multifaceted, which was inspired by the concept of atuação polifonica developed by the actor and researcher Ernani Maletta. Throughout this paper are presented some of the most recurrent skills required by percussionists in the current repertoire: learning techniques and instruments from the most diverse cultures, capacity to create and / or modify instruments, incorporation of elements of theatrical language (mainly use of gesture and voice ), knowledge of basic elements of technology. Finally, three works are presented and discussed, in which many of these skills are required of the performer: Silence must be!, by Thierry De Mey; Cinnabar Heart, of Chinnary Ung; and Double, by Aurélio Edler-Copes.